Colouration of textiles using roasted peanut skin- an agro processing residue. (20th January 2018) - Pandey, Ritu; Patel, Shweta; Pandit, Pintu; Nachimuthu, Shanmugam; Jose, Seiko
Abstract: Textile grade dye was extracted from roasted peanut skin ( Arachais hypogaea ) through aqueous extraction. The dye was characterised by phyto-chemical, uv visible spectroscopy and FTIR analysis. Cotton, silk and wool fabrics were dyed at different temperatures as well as using microwave energy without using any mordants. Dyed fabrics were assessed for their colour values, fastness properties and ultraviolet protection factor. All the fabrics shown good affinity for the dye. Uniform dyeing was observed in all fabrics; however, the dye exhaustion was higher in silk and wool than cotton. The dyed fabrics possessed good to very good fastness properties with and an ultraviolet protection factor up to 65. A comparative evaluation of synthetic dyes required to produce the same shade with that of peanut skin dye was also performed. Graphical abstract: Image 1 Highlights: Textile grade dye was extracted from roasted peanut skin-an agro processing waste. The dye was characterised by using various analytical methods. Cotton, wool and silk fabrics were dyed using the dye without using any mordents. The colour fastness properties of the dyed fabrics were found to be good. The dyed fabric possessed an ultraviolet protection factor up to 65.